Identification class of secondary metabolites in ethanolic extract of fruits and leaves of Eugenia uniflora L - Lima, Renato Abreu; Silva, Ana Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
This study aimed to conduct a preliminary phytochemical study of the ethanol extract of the leaves and fruits of E. uniflora. This work consisted of the plant collection in Porto Velho, and the preparations of the extracts were performed at the Phytochemical Laboratory, being done cleaning, sorting and weighing of the still fresh material, and taken to the greenhouse recirculation, for 48 to 72 hours at 50°C. Then she added 1 liter of ethanol for sheets and 350 mL of ethanol for fruit and left undisturbed for seven days. Subsequently, the material was subjected to simple distillation, and phytochemical test that consisted in the identification of secondary metabolites according to precipitation and coloration of extracts diluted in solution and specific reagents for each alkaloids test, cardiac glycosides, flavonoids, coumarins, tannins, triterpenes and saponins. Phytochemicals tests in ethanol extract of the leaves and fruits of E. uniflora showed the presence of alkaloids, cardiac glycosides, coumarins, flavonoids and tannins. However, negative results are saponins and triterpenes. It is concluded that the ethanol extract of the leaves and fruits of E. uniflora presents secondary metabolites that need to be tested in biological assays in vitro and in vivo.